Reaching The Customers: Role Of Multiple Delivery Channels In Banking Industry (Trinity Journal of Management, IT & Media (TJMITM), 2014)
The Indian banking industry plays an important role in the economic  development of the country and is the most dominant segment of the  financial sector. It is emerging as one of the fastest vehicle in the  panorama of the burgeoning service sector in India. Banking is  practically a necessity to business activity and is important for the  growth of the economy. It is the center point of the economy as it caters to  the need of all sections of the society. Attracting and retaining customers  is always a key focus area for banks to be successful. Banks are finding  new ways to reach their customers with a mix of traditional and modern  techniques. This has necessitated a vigorous distribution system to  reach out to customers across the expanse of a vast country especially in  India. There is a need of adapting a system with multiple delivery  channels which enables banks to expand their pool of potential  customers by appealing to a greater number of segments, and catering  to a wider range of needs. The present paper focuses on the multiple  delivery channels available to bank customers for various banking  services and it further examines the role of multiple delivery channels in  Banking Industry in India.
Keywords: Banking Industry; Attracting and retaining; Intermediary system; Bank Customers; Multiple Delivery Channels